2020
DOI: 10.1111/ijpo.12689
|View full text |Cite
|
Sign up to set email alerts
|

Increased adiposity in children with obesity is associated with low red blood cell omega‐3 fatty acid status and inadequate polyunsaturated fatty acid dietary intake

Abstract: Summary The association between total dietary fat intake and measures of body fatness in children with obesity remains inconsistent. This study aimed to determine whether dietary long‐chain polyunsaturated fatty acids (LCPUFA) and LCPUFA status relate to body composition in children with obesity. Children (n = 63, 9.0 ± 0.2 year, BMI Z‐score 3.1 ± 0.2) were divided into tertiles of percentage body fat assessed by dual‐energy X‐ray absorptiometry. Diet was assessed 3‐days food diaries. Fatty acid proportions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…There are no adequate standardized ranges for FA concentrations or percentages in children. Petersen et al refer, for children between 0 and 3 years old, healthy levels for DHA about 2–4%, similarly as other authors have reported ( 42 , 43 ). Moreover, Drover et al indicated that a DHA-standard concentration of 0.32% ensures an adequate cognitive function ( 44 ).…”
Section: Discussionsupporting
confidence: 78%
“…There are no adequate standardized ranges for FA concentrations or percentages in children. Petersen et al refer, for children between 0 and 3 years old, healthy levels for DHA about 2–4%, similarly as other authors have reported ( 42 , 43 ). Moreover, Drover et al indicated that a DHA-standard concentration of 0.32% ensures an adequate cognitive function ( 44 ).…”
Section: Discussionsupporting
confidence: 78%
“…Among the fatty acids assessed, docosahexaenoic acid was positively associated with lean mass and negatively with body fat. A previous study in children with obesity showed inverse associations between docosahexaenoic acid in red blood cells and % body fat [ 21 ]. On the contrary, the omega-6 fatty acid, linoleic acid, which has been identified as obesogenic [ 22 ], was associated with increased body fat and decreased lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…No significant associations were found between the obesity risk pattern and plasma and erythrocyte DHA, adjusting for the demographic characteristics. The previous studies demonstrated that children with obesity presented lower DHA statuses for erythrocyte [ 6 , 47 ]. However, children in the obesity risk pattern had a significant association with the plasma DHA concentration after adjusting for demographic variables and the intake of animal food products in this study.…”
Section: Discussionmentioning
confidence: 99%